Redistributive effect and progressivity of taxes: An international comparison across the EU using EUROMOD - Gerlinde Verbist (University of Essex, Institute for Social and Economic Research (ISER), 2004)
This paper gives an international comparison of the redistributive effect of personal income taxes in the 15 countries of the EU, using the European tax-benefit model EUROMOD. We focus on the effect of personal income taxes, social insurance contributions and other direct taxes. We present the contribution of progressivity and average tax rate to the reduction of income inequality, as well as the weight of the various types of tax concessions (i.e. exemptions, deductions, allowances and credits). There appears to be a wide variety among countries in the level of inequality reduction as well as in the instruments used to achieve this reduction. Personal income taxes are in all countries the most important source for inequality reduction, which is to a large extent, though not solely, due to the progressive rate schedule. Countries with a high degree of pre-tax inequality do not systematically redistribute more through their taxes; the results indicate rather the opposite.
Keywords: C81; D31; H23; H24; 330; income redistribution; income taxes; social insurance contributions; microsimulation; European Union